A very Harold & Kumar Christmas [videorecording (DVD)] - Strauss-Schulson, Todd, 1980-; Cho, John, 1972-; Penn, Kal, 1977-; Harris, Neil Patrick, 1973-; Oswalt, Patton, 1969- (Distributed by Warner Home Video, 2012)
Following years of growing apart, Harold Lee and Kumar Patel have replaced each other with new friends and are preparing for their respective Yuletide celebrations. But when a mysterious package mistakenly arrive at Kumar's door on Christmas Eve, his attempts to redirect it to Harold's house ends with the 'high grade' contents, and Harold's father-in-law's prize Christmas tree, going up in smoke.